1997
DOI: 10.1055/s-0038-1657531
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Dephosphorylation Mechanisms in Platelet Function: a Tightly Regulated Balance

Abstract: and pleckstrin @7 b,Da) (12). The hydrolysis of Pi Pz results also from the stimulation of Pl-Cywhich is independent of G protein and requires tyrosine kinase activity. 2) Thrombin Eeatment causes also a dramatic increase in the level of phosphotyrosines on multiple proteins which occur in three temporal waves (3,4), the third one being dependent on aIIbBr integrin engagement and plateletag gregation, since agents that block fibrinogen binding inhibit the tyrosine phosphorylation of the last wave. The increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 55 publications
1
28
1
Order By: Relevance
“…However, platelet interactions with a collagen-rich surface are related to deep vascular damage and acute thrombotic events, which could trigger a more intense cascade of signalling mechanisms [23]. Tyrosine phosphorylation of proteins is one of the signalling mechanisms that regulates cell responses [25], and which has been extensively studied in platelets activated in suspension [5,26]. Our present study has considered that platelets fulfil their main function by interacting with the subendothelium under flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, platelet interactions with a collagen-rich surface are related to deep vascular damage and acute thrombotic events, which could trigger a more intense cascade of signalling mechanisms [23]. Tyrosine phosphorylation of proteins is one of the signalling mechanisms that regulates cell responses [25], and which has been extensively studied in platelets activated in suspension [5,26]. Our present study has considered that platelets fulfil their main function by interacting with the subendothelium under flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In platelets, p38 MAPK is activated by stress, such as heat and osmotic shock, arsenite, H 2 O 2 , ␣-thrombin, collagen, and thromboxane analog (11,12), and is involved in the phosphorylation of [Ca 2ϩ ]-dependent cytosolic phospholipase A 2 (cPLA 2 ), with subsequent production of TXB 2 ( Figure 1). Thrombin has also been shown to induce phosphorylation of ERK-1/2, involving protein kinase C (PKC), phospholipase C␤ (PLC␤), and the intracellular mobilization of [Ca 2ϩ ] (Figure 1) (13)(14)(15). Although several studies have shown that aPL enhance platelet activation in vitro in the presence of low doses of agonists (ADP, thrombin, collagen, or TRAP) (7)(8)(9)(10)16), the intracellular events involved in this process are not understood.…”
mentioning
confidence: 99%
“…5). In these experimental settings, signaling as mediated by ␣ IIb ␤ 3 was shown to involve tyrosine kinases, including Syk, Fak, and Src, as well as tyrosine phosphatases, such as PTP1B (5,12,13). In contrast, signaling associated with clot retraction by platelets has been the subject of only a few reports.…”
mentioning
confidence: 99%